2017
DOI: 10.1080/02673843.2017.1371614
|View full text |Cite
|
Sign up to set email alerts
|

The effects of parenting styles on each personal growth initiative and self-esteem among Japanese university students

Abstract: a faculty of nutrition, Kagawa nutrition university, sakado, Japan; b faculty of letters, aichi university, toyohashi, Japan ABSTRACTThis study investigated the extent to which individual differences in personal growth initiative (PGI) and self-esteem are effected by parenting style. The sample consisted of 329 Japanese university students. The Parental Authority Questionnaire (PAQ) measuring three parenting styles (authoritative, authoritarian, and permissive), the PGI, and the self-esteem scale were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
(39 reference statements)
3
15
0
4
Order By: Relevance
“…Parents are the main and most intimate socialization agent fundamentally influential of youths’ various aspects of development, in which actions of parental figures performed and the socialization environments they created are generally referred as parental socialization [2,7,9]. Nevertheless, prior family research tended to treat parenting practices of parental caregivers tantamount to parental socialization, therefore overlooking the effects of other parental socialization facets on youth development [1,7,9]. Consonantly, recent research revealed that parental socialization is a multifaceted concept comprising of not only parenting behaviors but also family processes.…”
Section: Parental Socialization and Development Of Chinese Youthsmentioning
confidence: 99%
See 4 more Smart Citations
“…Parents are the main and most intimate socialization agent fundamentally influential of youths’ various aspects of development, in which actions of parental figures performed and the socialization environments they created are generally referred as parental socialization [2,7,9]. Nevertheless, prior family research tended to treat parenting practices of parental caregivers tantamount to parental socialization, therefore overlooking the effects of other parental socialization facets on youth development [1,7,9]. Consonantly, recent research revealed that parental socialization is a multifaceted concept comprising of not only parenting behaviors but also family processes.…”
Section: Parental Socialization and Development Of Chinese Youthsmentioning
confidence: 99%
“…Specifically, authoritative parenting, as demonstrating both high parental demandingness and responsiveness concurrently, has been corroborated to positively contribute to youths’ establishment a self-identity of worth, competence and respect, development of cognitive and psychological strengths, and decrease of mental health problems and behavioral maladjustment [1,4,6,12]. Conceptually, social learning theory and social control theory can help explain the beneficial effects of authoritative parenting on youth development, in which youths’ self-concept, value orientations, cognitive approaches, psychological traits and behavioral choices are cultivated in the processes of social learning and controlling and parents are the prime socialization agent to foster and steer development of their youth children by instructions, rules, directions, support and expectations set in their parenting practices [1,14,15]. Empirically, Hirata and Kamakura (2018) found that authoritative parenting was significantly related to higher personal growth initiative and self-esteem among university students and such relationships did not exist in authoritarian and permissive parenting styles.…”
Section: Parental Socialization and Development Of Chinese Youthsmentioning
confidence: 99%
See 3 more Smart Citations